Mosque energy efficiency and designer's approaches towards MS1525 / Tengku Anis Qarihah Raja Abdul Kadir, Maisarah Ali and Wan Nur Rukiah Mohd Arshard - Raja Abdul Kadir, Tengku Anis Qarihah; Ali, Maisarah; Mohd Arshard, Wan Nur Rukiah (2022)
Several concepts and approaches have emerged throughout the last decades concerning energy efficiency in buildings, including passive houses, green buildings, and bioclimatic design. Every country begins to consider how to cut energy usage and work toward a carbon-free future. The built environment is one of the most significant contributors to high energy use. New legislation, codes of practice, standards, and incentives have been initiated to enforce energy efficiency in buildings in some nations. This exploratory study will investigate 'passive design methods' in the Malaysian setting, reducing, and minimizing energy consumption to meet the Malaysian Standard MS 1525. In expediting and implementing the MS 1525, the valuable design information on the selection and arrangement of various components in the early building design process is beneficial. It helps implement optimization techniques of passive design strategies that could aid building designers in their decision-making process to achieve optimum thermal performance. Proper treatment of building envelope contributes to the improvement of the building. Therefore, this study will analyse and measure the current building design and materials concerning MS 1525 and focus on the mosque as the case study. Mosques have high working schedules, prayer times, and activities, which require the buildings operation to be working 24/7. The Malaysian Standard MS1525, designers are required to consider energy efficiency and be prudent when constructing buildings, particularly those with large volumes and gross floor areas. Passive design solutions that are effective may help reduce wastage while also reducing energy consumption in a building compared to this benchmark. The outcomes of this research will help determine and measure the success rate of our designers to implement and adopt Malaysian Standard 1525.